Sekresi Asam-asam Organik oleh Aspergillus niger YD 17 yang Ditumbuhkan dengan Batuan Fosfat - Sastro, Yudi; Widianto, Donny; Shiddieq, Dja'far (Biota : Jurnal Ilmiah Ilmu-Ilmu Hayati, 2006)
Information on ability of Aspergillus niger to secrete organic acid is important in using A. niger as phosphate rock-solubilizing microorganism. This research was aimed to examine the ability of A. niger YD 17 secreting organic acid when it was grown with phosphate rock. An A. niger YD 17 was obtained from Laboratory of Microbiology, Faculty of Agriculture, GMU. The phosphate rock used was Christmas Island phosphate rock. Organic materials consisted of tapioca waste industry, rice bran, and starch. The study was conducted in Pikovskaya liquid medium and soils that were taken from Jasinga, Banten, West Java (ultisol) and Karang Jati, Ungaran, Central Java (inceptisol). The type and level of organic acid production were determined using high performance liquid chromatography (HPLC). The results indicated that A. niger YD 17 was able to secrete organic acid when it was grown with phosphate rock. The level of organic acid in the Pikovskaya liquid medium reached 255.7 ïg.ml-1, whereas in the soil reached 2992.5 ïg.g-1. Malate dominated organic acid in the Pikovskaya liquid medium, while in the soils dominated by oxalate. The type and level of organic acid secreted by A. niger YD 17 were influenced by carbon and phosphorus sources, concentration of inoculums, and characteristic of the soils.